Regulation of Securitised Products post the Financial Crisis - Hans von Reden (UCL Journal of Law and Jurisprudence, 2015)
Securitisation has been one of the main reasons for the global financial crisis. The securitisation business has experienced a steep decline for two decades until an even stronger decline in the summer of 2007. This article analyses the regulatory developments in the structured market and the measures taken by legislators since the crisis to address the shortcomings in the securitisation market. The main problems are centred around four areas, which are analysed separately: first, misalignment of interests between investors and originators; second, inadequate capital rules failing to reflect the actual risk exposures; third, insufficient disclosure and information overload of investors; and fourth, credit rating agencies failing to give quality ratings. It concludes that while the adopted regulatory measures might have less corrective effects than envisaged, this is favourable as long as the precise consequences of the adopted measures are not clear. Read more